EFEKTIFITAS TERAPI MUSIK ISLAMI TERHADAP PENURUNAN INTENSITAS NYERI PADA IBU POST SECTIO CAESAREA DI RSUD PURI HUSADA TEMBILAHAN - Nurul Indah Sari (Jurnal Kesehatan Husada Gemilang, 2018)
Sectio caesarea is a process of childbirth by performing a surgical incision that penetrates the mother's abdomen to remove one or more children and this method is done when vaginal delivery will lead to complications. Labor with section caesarea often experiences pain due to abdominal incision. One of non-pharmacological action to reduce pain is Islamic music therapy. This research was conducted on the aim of clarifying the effectiveness of Islamic music therapy in reducing pain intensity in post sectio caesarea mothers at Public Hospital of Puri Husada Tembilahan. This research is a quantitative research with a quasi-experiment design (one group pre-test and posttest) with 35 respondents, the sample is taken through total sampling technique. The results of nonparametric statistical test which are gained thru the Wilcoxon test with a 95% valid (α = <0, 05) is P value = 0,000, Ha is accordingly accepted – Islamic music therapy is effective in reducing pain intensity in post sectio caesarea mothers in Public Hospital of Puri Husada Tembilahan. It can be inferred that Islamic music therapy is effective in reducing pain intensity in mothers post sectio caesarea. For the reason, it is recommended to use Islamic music therapy as an alternative to non-pharmacological pain handling, especially those who experience pain at post sectio caesarea.